2008
DOI: 10.3758/pbr.15.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Causal diversity effects in information seeking

Abstract: When trying to determine the root cause of an observed effect, people may seek out information with which to test a candidate hypothesis. In two studies, we investigated how knowledge of causal structure influences this information-seeking process. Specifically, we asked whether people would choose to test for pieces of evidence that were far apart or close together in the learned causal structure of a disease category. In parallel with findings showing people's tendency to select diverse evidence in argument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…However, when the task is easy enough, children can choose the more useful strategy (the observed diversity eff ect). A similar pattern has been found in adults, when negative diversity eff ects were observed in adult populations ( Lόpez, et al , 1997 ;Kim & Keil, 2003 ;Kincannon & Spellman, 2003 ;Heit & Feeney, 2005 ;Kim, et al , 2008 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, when the task is easy enough, children can choose the more useful strategy (the observed diversity eff ect). A similar pattern has been found in adults, when negative diversity eff ects were observed in adult populations ( Lόpez, et al , 1997 ;Kim & Keil, 2003 ;Kincannon & Spellman, 2003 ;Heit & Feeney, 2005 ;Kim, et al , 2008 ).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies showed that adults' reactions to the diversity of evidence in inductive reasoning are stable, except under limited conditions ( Lόpez, 1995 ;Kim & Keil, 2003 ;Kincannon & Spellman, 2003 ;Heit & Feeney, 2005 ;Kim, Yopchick, & Kwaadsteniet, 2008 ), e.g., tree experts did not show a diversity eff ect when they were reasoning about trees and their diseases ( Proffi tt, Coley, & Medin, 2000 ), but they were more likely relying on their knowledge about transmission of tree diseases rather than the knowledge of taxonomy. Prior experimental evidences of children's reactions to the diversity samples, however, have been even more mixed ( Hayes, et al , 2010 ).…”
Section: Developmental Evidence Of the Diversity Eff Ectmentioning
confidence: 99%
“…This additional layer within the hierarchy of health information consultation may result in a reinforcement effect, providing singers with extra confirmation of the validity of the information revealed by their search. 16 Consistent with the Pew findings, female singers were more likely to search for voice-related health information than male singers (P ¼ 0.0135). However, whereas the Pew findings showed that younger people were more likely to support the credibility of the health-related information they found, their cohorts among the community of classical singers were more likely to be skeptical about information validity than older participants (P ¼ 0.0483).…”
Section: Health Information Seekingsupporting
confidence: 83%
“…Such information-seeking offsets any credibility or accessibility problems embedded in the various information sources (Burkell et al, 2006). Seeking health information from diverse sources also allows the pregnant woman to confirm her understanding about a health situation and/or to remove doubts (Kim & Yopchick, 2008). Health informationseeking in this study referred to convergent information-seeking.…”
Section: Introductionmentioning
confidence: 98%